Actual share repurchases, timing and liquidity - Ginglinger, Edith; Hamon, Jacques (Journal of Banking & Finance, 2007)
Research on the impact of open market share repurchases has been hindered by the lack of data available on actual share repurchases in many countries, including the US. Using a previously unused database containing detailed information on 36,848 repurchases made by 352 French firms, we show that corporate share repurchases have a significant adverse effect on liquidity as measured by bid–ask spread or depth. Our results also indicate that share repurchases largely reflect contrarian trading rather than managerial timing ability.